A circulating anticoagulant inhibiting antihaemophilic globulin. Issue 3 (May 1965) - Pinkerton, P. H.; Dagg, J. H.; Taylor, Frances
Abstract : A circulating anticoagulant inhibiting antihaemophilic globulin (A.H.G.) is described in an otherwise healthy 70-year-old woman, and the therapeutic response to steroids is discussed. The nature and pathogenesis of the anticoagulant remain obscure, but its properties and behaviour do not support an autoimmune aetiology.